2020
DOI: 10.1177/1526602820960445
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes of Heparin-Bonded Stent-Graft Therapy for Real-World Femoropopliteal Lesions and the Association of Patency With the Prothrombotic State Based on the Prospective, Observational, Multicenter Viabahn Stent-Graft Placement for Femoropopliteal Diseases Requiring Endovascular Therapy (VANQUISH) Study

Abstract: Purpose: To evaluate the real-world primary patency of heparin-bonded stent-graft therapy for femoropopliteal (FP) occlusive disease and identify any clinical factors, including the prothrombotic state, associated with the loss of patency. Materials and Methods: This multicenter study prospectively enrolled 424 limbs of 371 patients (mean age 75±8 years; 247 men) scheduled for Viabahn stent-graft placement in the FP segment. A full-coverage strategy using only a Viabahn stent-graft was preferred, but “spot ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…As for endovascular techniques in the treatment of reaction unit (PRU) values, a marker of the resistance on P2Y12 inhibition (antiplatelet effect), after the stent-grafting of patients with symptomatic PAD presenting femoropopliteal artery lesions. The study also found no relationship between PRU values and vessel patency 47) , suggesting that the effect of antiplatelet therapy would have a small, if any, influence on vessel patency. Clinical attention is shifting from the intensification of antiplatelet therapy to the introduction of DOACs.…”
Section: ) Revascularization Strategy (Surgical or Endovascular Approach) I Revascularization For Aortoiliac Lesionsmentioning
confidence: 62%
“…As for endovascular techniques in the treatment of reaction unit (PRU) values, a marker of the resistance on P2Y12 inhibition (antiplatelet effect), after the stent-grafting of patients with symptomatic PAD presenting femoropopliteal artery lesions. The study also found no relationship between PRU values and vessel patency 47) , suggesting that the effect of antiplatelet therapy would have a small, if any, influence on vessel patency. Clinical attention is shifting from the intensification of antiplatelet therapy to the introduction of DOACs.…”
Section: ) Revascularization Strategy (Surgical or Endovascular Approach) I Revascularization For Aortoiliac Lesionsmentioning
confidence: 62%
“…Iida et al reported that IVUS use in femoropopliteal stenting appears to be associated not only with the procedure's success but also with a higher primary patency rate 56 . Previous reports were based on the IVUS evaluation methodology, such as vessel size, lumen area, wire route, calcification, lesion morphology, and vessel dissection after balloon angioplasty (Iida et al 2021;Kozuki et al 2021;Kurata et al 2020;Miki et al 2020a;Miki et al 2020b). Some parameters that influenced patency outcomes were shown, including calcification, vessel dissection, and post stent area and position (Iida et al 2015;Mori et al 2017;Norgren et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…If the authors did not respond, after a second email, the study was excluded. Seven authors responded positively and agreed to join and signed clinical investigation and data transfer agreements 5,6,8,11–14 . Six authors did not respond to either the first or second email.…”
Section: Methodsmentioning
confidence: 99%